KARYOMORPHOLOGICAL CHARACTERIZATION OF SOME WILD SPECIES OF SOLANUM - AJOY KUMAR DAS; SAILENDRA PRASAD BORAH (International Journal of Pharma and Bio Sciences, 2015)
North East India is one of the mega biodiversity hot spot, also one of the richest reservoir of genetic variability and diversity of different crops. Here, natural distribution of non tuberous Solanum species is also found to be very rich. Despite the importance of Solanum species no information in the karyotype of the members of this taxa available in North East India is found. In the present investigation, a comparision was made between the karyotypes of six important species of the genus Solanum (Viz. S. torvum Swartz., S. ferox Linn., S. nigrum Linn., S. kurzii Br., S. Sysimbrifolium Lam. and S. xanthocarpum Schrad. and Wendl.) available in this region of India to interpret the karyomorphological interrelation and affinity among themselves. The karyotype analysis of Solanum kurzii Br. which is endemic to this region is reported for the first time. All the species under study have chromosome number 2n= 24. The longest chromosome with 3.80 µm length was observed in Solanum sisymbrifolium Lam. and the smallest one with a length of 0.50 µm was observed in Solanum xanthocarpum Schrad. and Wendl. With respect to chromosome morphology the karyotype of these species have a majority of metacentric and submetacentric chromosomes.